THE EVALUATION OF TEACHER PROFESSIONAL EDUCATION PROGRAM BACHELOR OF EDUCATION IN THE FOREMOST, OUTER AND BEHIND PROGRAM THE EDUCATION OF PHYSICAL, HEALTH AND RECREATION IN STATE UNIVERSITY OF JAKARTA - Iwan Setiawan (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2018)
This study aims to evaluate the Teacher Professional Education Program Bachelor of Education In The Foremost, Outer And Behind program in Jakarta State University. The research of Teacher Professional Education Program Bachelor of Education In The Foremost, Outer And Behind program evaluation used CIPP model of Daniel L. Suffebeam because this approach fits the research objectives describing the Teacher Professional Education Program Bachelor of Education In The Foremost, Outer And Behind program. The instruments used were the researcher himself, interview guidance, questionnaires, and documentation. Data analysis was done in accordance with Miles and Huberman namely; data reduction, data display, and conclusion. The results found were: 1) context aspect namely: that Teacher Professional Education Program Bachelor of Education In The Foremost, Outer And Behind program had agreed with the objectives, had a strong legal basis, and needs analysis namely to assist the acceleration of government programs for equitable education; 2) input aspects namely: program plan and facilities in the form of human resources such as lecturers, Teacher Professional Education Program participants, facilities and infrastructure, funding, partnership and management were available well according to the plan; 3) process aspects, namely the implementation of the activities, including: the implementation of the evaluation process, decision-making process, learning process, and graduation process had already run well; 4) product aspects namely Teacher Professional Education Program Bachelor Of Education In The Foremost, Outer And Behind Program of Education of Physical, Health and Recreation study program of Jakarta State University had been able to improve the quality and quantity of participants, including the number of graduates. Based on the results of this evaluation, it can be concluded that Teacher Professional Education Program Bachelor of Education In The Foremost, Outer And Behind program had been implemented as well as possible but it needed improvement of facilities and infrastructure, funds, and coordination between the ministry of research and technology of higher education and Teacher Training Institute of Jakarta State University. Keywords: Program Evaluation, Teacher Professional Education Program Bachelor of Education In The Foremost, Outer And Behind, CIPP Model, and Education of Physical, Health and Recreation.